2020
DOI: 10.3389/fendo.2020.571357
|View full text |Cite
|
Sign up to set email alerts
|

Increased MicroRNA Levels in Women With Polycystic Ovarian Syndrome but Without Insulin Resistance: A Pilot Prospective Study

Abstract: Background: Small noncoding microRNA (miRNA) have regulatory functions in polycystic ovary syndrome (PCOS) that differ to those in women without PCOS. However, little is known about miRNA expression in women with PCOS who are not insulin resistant (IR). Methods: Circulating miRNAs were measured using quantitative polymerase chain reaction (qPCR) in 24 non-obese BMI and age matched women with PCOS and 24 control women. A miRNA data set was used to determine miRNA levels. Results: Women with PCOS showed a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Let-7b-3p, previously known as let-7b, was conventionally regarded as the passenger strand was considered to have no biological function. In recent years, however, relevant studies have revealed let-7b-3p to play a significant role in various of diseases (13)(14)(15). Despite this, the specific role and mechanism of let-7b-3p in LUAD remains unclear.…”
Section: Original Articlementioning
confidence: 99%
“…Let-7b-3p, previously known as let-7b, was conventionally regarded as the passenger strand was considered to have no biological function. In recent years, however, relevant studies have revealed let-7b-3p to play a significant role in various of diseases (13)(14)(15). Despite this, the specific role and mechanism of let-7b-3p in LUAD remains unclear.…”
Section: Original Articlementioning
confidence: 99%
“…Down‐regulated in young women with PCOS ( n = 24). 43 No difference between obese ( n = 21) and NW ( n = 19) women but correlated with waist circumference 102 …”
Section: Resultsmentioning
confidence: 99%
“…Up‐regulated in PCOS 43 and relapsing multiple sclerosis (MS), may be involved in inflammatory pathways 44 …”
Section: Resultsmentioning
confidence: 99%
“…Due to the low concentration of cell-free circulating RNAs in biofluids such as plasma, precise estimation of RNA concentration is challenging. In this study, RT was performed using equal volume of RNA originating from the equal volume of plasma as described by previous studies (Blondal et al, 2013;Cook et al, 2019;Butler et al, 2020). RT for plasma miRNAs was performed using 2 µl RNA template in 10 µl total RT reaction volume using miRCURY LNA ™ Universal RT miRNA cDNA synthesis kit II (Exiqon), with the addition of 0.625 µl spike-in of synthetic miRNA, UniSp6 (10 8 copies/µl) (Exiqon) for normalization of variation in the RT process.…”
Section: Rna Extraction and Rt-qpcrmentioning
confidence: 99%